Artificial intelligence at the workplace and the impacts on work organisation, working conditions and ethics - Lucie Lechardoy; Laura López Forés; Cristiano Codagnone (International Telecommunications Society (ITS), 2023)
The Digital Compass sets the goal to increase the digitalisation of businesses and take-up of artificial intelligence (AI). The use of AI-based technologies, such as algorithmic management, AI-based robots and wearables using algorithms for data processing, is increasing across countries and sectors. Based on a literature review and the insight from exploratory case studies at company level, this paper presents the main applications of AI-based technologies at the workplace and their impacts for work organisation, working conditions and ethics. Evidence shows a range of both positive and negative impacts of the use of AI on work organisation and working conditions as well as several ethical concerns. To address some of these concerns, a set of ethical guidelines and recommendations from EU, international and national public authorities and social partners have emerged in recent years. The paper presents and compares the different initiatives, highlighting the current gaps to ensure the protection of workers and working conditions while contributing towards the digitalisation goals of the Digital Compass.
Keywords: 330; Artificial intelligence; workplace; impacts; work organisation; working conditions; ethics; legislative framework